Analysis of Bank Soundness Level at Regional Development Bank of Bali for 2012 to 2021 - I Kadek Bagiana; Luh Pande Eka Setiawati; RR. Maria Yulia Dwi Rengganis; Anak Agung Sagung Istri Pramanaswari (Universitas Batanghari Jambi, 2023)
The purpose of this study is to analyze the health level at RDB of Bali by using the Risk Based Bank Rating (RBBR) method. The RBBR method includes Risk Profile, Good Corporate Governance, Earnings, and Capital (RGEC). A quantitative descriptive approach was used to analyze. The variables in this study are the Risk Profile includes the ratio of Non Performing Loans (NPL) and Loan to Deposit Ratio (LDR), Good Corporate Governance (GCG) uses the composite value of GCG, Earnings includes the ratio of Return on Assets (ROA) and Net Interest Margin (NIM) and Capital includes the Capital Adequacy Ratio (CAR). Data were collected from annual reports for the period 2012 to 2021. The results showed that RDB of Bali obtained a composite rating of 2, which means the bank is in a healthy condition.